QUALITY ASSURANCE AND STANDARDS OFFICER’S SCHOOL CURRICULUM ASSESSMENT AND STUDENTS’ ACADEMIC PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN TRANS-NZOIA WEST SUB-COUNTY, KENYA - Lukorito, Godfrey; Ngome , Charles K.; Kikechi, Ronald Werunga (IJRDO- Journal of Educational Research, 2023)
The purpose of the study was to establish the relationship between QASO’s school curriculum Assessment and students’ academic performance in public secondary schools in Trans-Nzoia West Sub-County. The study employed descriptive research design with a target population of 1439 persons. A sample size of 313 was determined using Yamane formula for determining sample sizes. The researcher collected data using questionnaires and interviews guides. The instruments were validated by the supervisors. Reliability of the instruments was determined through a pilot study where Cronbach alpha coefficients of 0.741, 0.771 and 0.736 were obtained for the instruments on teacher trainings organized by QASO’s, QASO’s school curriculum assessment and QASO’s school physical facilities assessments respectively. This indicated that the instruments were reliable. Quantitative data was analyzed using descriptive statistics and inferential statistics and presented in graphs and tables, while qualitative data from interviews was organized into themes and sub-themes. The study established that teacher training organized by QASO’s, QASO’s school curriculum assessments and QASO’s school physical facilities assessments had a significant relationship with students’ academic performance. It was therefore recommended that to enhance students’ academic performance, there should be more teacher training organized by QASO’s, regular QASO’s school curriculum assessments and adequate school physical facilities assessments by QASO’s.